Member Satisfaction Level With Service Performance of Kud Surya Adi in Helping Oil Palm Farmers in Mesuji District Ogan Komering Ilir District - Ardiyansyah, Aexs; Batubara, Mustopa Marli; Afriyatna, Sisva Berty (Journal of Agricultural Studies, 2022)
This study aims to determine how the performance of Surya Adi KUD services to members and to determine the level of member satisfaction with the performance of services provided by Surya Adi KUD. The research implementation time is from October 2021 to December 2021. The method used in this research is a survey method, which aims to see the situation that is the object of research as it really is, by looking at the data and information in the sample, without giving special treatment. The sample in this study were members of KUD Surya Adi totaling 54 people. The results showed that the performance of KUD Surya Adi management was based on the distribution of each attribute, namely Physical Evidence (Tangible), Reliability (Reliability), Responsiveness (Responsive), Guarantee and Certainty (Assurance), and Giving Attention (Emphaty).), in accordance with members’ expectations, but for the Important Performance Analysis (IPA) method of analysis there are still 9 (nine) distributions that must be improved, and members are satisfied with the service performance of Surya Adi KUD. This can be seen from the test using the Customer Satisfaction Index (CSI) analysis method with a score of 0.74 in the satisfied category.